2006
DOI: 10.1038/sj.bjp.0706765
|View full text |Cite
|
Sign up to set email alerts
|

Local regulation of skin blood flow during cooling involving presynaptic P2 purinoceptors in rats

Abstract: 1 This study investigated a local effect of cooling on the plantar skin blood flow (PSBF) of tetrodotoxin-treated rats by laser-Doppler flowmetry. 2 When the air temperature around the left foot was locally cooled from 25 to 101C, the PSBF of the left foot decreased. 3 The response was inhibited by the a-adrenoceptor antagonist phentolamine, the a 1 -adrenoceptor antagonist bunazosin, the a 2 -adrenoceptor antagonist RS79948, and bretylium and guanethidine that inhibit noradrenaline release from sympathetic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…In a later paper, it was suggested that cooling-induced reduction in skin blood flow was because of the ATP released from sympathetic nerves stimulating presynaptic P2 receptors on sympathetic nerve terminals to facilitate release of noradrenaline, resulting in constriction (Koganezawa et al, 2006). When skin temperature was increased, A 1 receptors mediated vasodilation (Stojanov and Proctor, 1990).…”
Section: Skin Vesselsmentioning
confidence: 96%
“…In a later paper, it was suggested that cooling-induced reduction in skin blood flow was because of the ATP released from sympathetic nerves stimulating presynaptic P2 receptors on sympathetic nerve terminals to facilitate release of noradrenaline, resulting in constriction (Koganezawa et al, 2006). When skin temperature was increased, A 1 receptors mediated vasodilation (Stojanov and Proctor, 1990).…”
Section: Skin Vesselsmentioning
confidence: 96%
“…According to Koganezawa et al (2006), it was suggested that the cooling-induced reduction in skin blood flow was due to the ATP released from sympathetic nerves stimulating presynaptic P2 receptors on sympathetic nerve terminals to facilitate release of NA, resulting in constriction. Arteriolar contractile responses to nanomolar concentrations of topically applied adenosine acting at A 1 receptors in the skin microcirculation of hamsters were enhanced when local skin temperature was increased; vasodilator responses evoked by micromolar concentrations of adenosine were temperature insensitive (Stojanov and Proctor, 1990).…”
Section: G Skin Vesselsmentioning
confidence: 99%
“…Raynaud's Disease A physiological role for facilitatory P2 receptors in sympathetic nerves has been described, mainly in cooling-induced vasoconstriction in the skin (Koganezawa et al 2006). Cooling was shown to cause release of ATP that activated excitatory presynaptic P2 receptors in sympathetic nerve terminals to enhance NA release leading to vasoconstriction.…”
Section: Atherosclerosismentioning
confidence: 99%